Die anthropogene Beeinflussung der Wälder im westlichen Mittelmeerraum unter besonderer Berücksichtigung der Aufforstungen - Müller-Hohenstein, Klaus (ERDKUNDE, 1973)
The natural woodland cover of the western Mediterranean is composed of a large number of typical forest communities, whose spatial pattern is best studied with the help of planetary and hypsometric changes in form. Today in the western Mediterranean, only small remnants of seminatural forest communities have been preserved. The human influence on the woodlands, which stretches back to the fifth millenium B. C. has, in the course of time, not only led to extensive deforestation but also to the formation of characteristic substitute communities, whose differentiation can be related to the nature, intensity and duration of human influence. Since the beginning of the 20th century, in particular during the last two decades, afforestation has become more important for the forest cover of the countries of the Iberian Peninsula and the Maghreb dealt with in this paper. It is hoped that the results of these usually very expensive projects and campaigns will be not only an adequate provision of timber products, but also the creation of secure jobs. It is, however, certain that afforestation brings anthropogenic influences of a completely new order for the forest cover. The composition and distribution of recent forests and their position within the natural forest zonation and gradation is discussed with reference to specific examples.